Factors that Affect the implementation of Teaching Writing Skills: Focus on Second Cycle Primary Schools in North Shoa - Seid Mohammed; Gessese Nigusse; Zenawi Nigussie; Belihu Zenebe (Journal La Sociale, 2021)
The purpose of this study was to determine the variables affecting the implementation of writing skills instruction and learning in grades 7 and 8 in North Shoa Zone Second Cycle Primary schools. The study's primary purpose was to determine the difficulties encountered by English language instructors and students while teaching and learning to write in English classes. The research included the participation of 25 English language instructors and 1484 pupils from 14 Second Cycle Primary Schools. A questionnaire and an interview were used to obtain the required data. Questionnaires were completed by instructors and students, and English language teachers were interviewed. The questionnaire data was tallied and examined statistically in terms of frequency and percentage. Similarly, interview data were categorized and qualitatively characterized. The investigation revealed that the majority of instructors and students struggle with teaching and learning writing skills. Additionally, although both English instructors and students believe they are engaging in writing activities in the classroom, the students' writing performance is not as promising as shown by open-ended questions and comments from English language teachers interviewed. Several key suggestions are made in light of the results of this research in order to mitigate the issues that impede the efficient implementation of writing instruction and learning in second cycle primary schools. The primary recommendation is to offer enough training for English language instructors on how to teach writing skills, which will then be conveyed to students in order for them to enhance their writing performance.